Tingkat Resiliensi Anak Penyintas Pelecehan Seksual - Wahyu Nanda Eka Saputra; M. Fahri Hamdika Putra; Mimit Pakasi (Jurnal Ilmiah Tarbiyah Umat, 2024)
This research aims to investigate the level of resilience of children as survivors of sexual abuse, with a focus on comparing the level of resilience between boys and girls. The method used in this research is a literature review, by collecting and analyzing findings from various related studies. The research results show that, in general, child survivors of sexual abuse have a significant level of resilience, despite experiencing serious trauma. This depends on external factors such as friends, environment and family.